2018
DOI: 10.3389/fmicb.2018.03191
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bacterial Community Characteristics, Abundance of Antibiotics and Antibiotic Resistance Genes Along a Pollution Gradient of Ba River in Xi’an, China

Abstract: The microbial communities in freshwater have raised concerns about the ecosystem and human health. Many ecological environmental problems have been found in urban river because of the unreasonable use and long-term wastewater discharge. In this study, we explored the bacterial community composition, abundance of 14 antibiotics and 21 antibiotic resistance genes (ARGs), and water environment features in seven water samples and seven sediment samples from Ba River in Xi’an, China. Results showed Proteobacteria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 53 publications
1
22
2
Order By: Relevance
“…It is worth noting that the sediment community features a unique phylum WS3, also known as the candidate phylum ‘ Latescibacteria ’. This is consistent with previous studies on freshwater sediment (Morrison et al ., 2017; Guan et al ., 2018). Another study derived from single‐cell amplified genomes of WS3 indicates their heterotrophic and strictly fermentative lifestyle and suggested that it may play a crucial role in the turnover of algal detritus (Farag et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the sediment community features a unique phylum WS3, also known as the candidate phylum ‘ Latescibacteria ’. This is consistent with previous studies on freshwater sediment (Morrison et al ., 2017; Guan et al ., 2018). Another study derived from single‐cell amplified genomes of WS3 indicates their heterotrophic and strictly fermentative lifestyle and suggested that it may play a crucial role in the turnover of algal detritus (Farag et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, there were 128 duplicates, and 16,013 were excluded on the basis of title and abstract screening. A total of 68 studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , ...…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Figure 4 A, natural waters presented a higher abundance of Firmicutes (22%) and Bacteroidetes (20%), while in artificial waters, Bacteroidetes (25%), Firmicutes (21%) and α-Proteobacateria (22%) were the most representative. The predominance of these phyla was to be expected since they are widely distributed in the environment, including in the intestinal tracts of humans and animals, and in soil, sediments and water [ 3 , 12 , 18 , 24 , 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations